2014
DOI: 10.1007/s10637-014-0092-7
|View full text |Cite
|
Sign up to set email alerts
|

Kidney injuries related to ipilimumab

Abstract: Monoclonal antibodies directed against the immune checkpoint protein cytotoxic T-lymphocyte antigen-4 (CTLA-4; CD152) have been investigated in metastatic melanoma and other cancers and have shown promising results. Inhibition of CTLA-4 characteristically induces well-known side effects called "immune-related adverse events" (irAEs). IrAEs mainly include colitis, dermatitis, hepatitis, endocrinopathies; uveitis, iridocyclitis, neuropathies, and inflammatory myopathy have occasionally been reported. Kidney invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(119 citation statements)
references
References 19 publications
2
104
0
13
Order By: Relevance
“…irAEs can affect any organ system, but typically include the skin, the gastrointestinal (GI) tract, and the hepatic, endocrine and respiratory systems [35]. Other rare events such as uveitis, pancreatitis, hematological events, neurologic adverse events, and nephritis have also been reported [36,37,38,39,40]. In general, irAEs are manageable by the use of immunosuppressive therapy (e.g.…”
Section: Managing Toxicity and Side-effects Of Pd-1- And Pd-l1-directmentioning
confidence: 99%
“…irAEs can affect any organ system, but typically include the skin, the gastrointestinal (GI) tract, and the hepatic, endocrine and respiratory systems [35]. Other rare events such as uveitis, pancreatitis, hematological events, neurologic adverse events, and nephritis have also been reported [36,37,38,39,40]. In general, irAEs are manageable by the use of immunosuppressive therapy (e.g.…”
Section: Managing Toxicity and Side-effects Of Pd-1- And Pd-l1-directmentioning
confidence: 99%
“…Cell-mediated immune response leading to inflammatory cell infiltrates with and without granulomas has been reported [15,16]. Cases of acute interstitial nephritis (AIN) in the initial trials, arising 2-12 weeks post drug administration have been reported and one of them demonstrated granulomas [12,17,18,19,20,21,22]. The largest series of biopsy-proven cases of AKI was reported by Cortazar et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…Other rare irAEs related to checkpoint blockade include episcleritis, conjunctivitis, uveitis (51), neurologic adverse effects (52), increase of amylase and lipase, diabetes, pancreatitis (21,41), hematologic adverse effects (i.e., cytopenia, red cell aplasia, autoimmune neutropenia, acquired haemophilia A) (36,53,54), nephritis, glomerular lupus-like nephropathy and renal dysfunction (<1%, presenting after 10 months) (41,55) and pneumonitis. Pneumonitis is notable, because rare treatment-related deaths have been experienced in early clinical studies of PD-1 blockade (4).…”
Section: Delayed Treatment Effectmentioning
confidence: 99%